Charge Density Depinning in Defective MoTe2 Transistor by Oxygen Intercalation. (13th September 2020) - Liu, Xiaochi; Qu, Deshun; Wang, Lu; Huang, Ming; Yuan, Yahua; Chen, Peng; Qu, Yuanyuan; Sun, Jian; Yoo, Won Jong
Abstract: Molybdenum ditelluride is prone to various defects. Among them, tellurium vacancies lead to the significant reduction of band gap as revealed by density functional theory (DFT) calculations. They are responsible for inducing spatial band structure variation and localized charge puddles in MoTe2 . As a result, undesirable charge density pinning is anticipated in the channel‐dominated MoTe2 field‐effect transistors (FETs) even with much improved ohmic contacts, resulting in poor device characteristics, for example, conductivity minimum point (CMP) pinning and weak gate tunability. DFT simulations suggest occupying tellurium vacancies with oxygen can effectively restore MoTe2 to its intrinsic properties and therefore remove charge density pinning. Experimentally, this can be realized by oxygen intercalation during low‐pressure annealing without bringing in additional defects to MoTe2 . The CMP is unpinned in the FETs made of annealed MoTe2, which can be tuned by changing the contact metals with varied work functions. Moreover, much improved device characteristics, for example, a high hole current density exceeding 20 μAμm −1, a record high hole mobility of 77 cm 2 V −1 s −1, are obtained. Abstract : Mid‐gap states and the associated charge density pinning in defective MoTe2 with tellurium vacancies are responsible for the pinning‐like characteristics in its field effect transistors. Controlled thermal annealing induced oxygen intercalation is demonstrated to selectively address the vacancies without introducing additional oxidation, with which charge density can be effectively depinned.